EXPRESSION OF CONCERN: Research on Portable Intelligent Terminal and APP Application Analysis and Intelligent Monitoring Method of College Students’ Health Status - Li, Yu; Gao, Yuetong (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: https://doi.org/10.4108/eetpht.11.12709